The Influence Of Advertising And Social Media Toward Sales Improvement With Product Halalness As An Intervening - Utomo, Fahman Hadi; Rizkiawan, Ilham Karin (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This research has several main reasons of urgency, namely the Development of Digital Marketing Advertising and social media have become dominant factors in modern marketing strategies. The purpose of this study is to analyze how marketing strategies through advertising and the use of social media can increase sales of a product, especially in the beauty industry. This research is quantitative because it focuses on measuring the relationship between variables using numerical data and statistical analysis. This study uses a causal model to test the effect of advertising and social media on sales, with product halalness as an intervening variable. This model can be analyzed using Structural Equation Modeling (SEM-PLS) or multiple regression. The population is Ms Glow Beauty consumers who have used the product and are exposed to advertising and social media. The sample is determined using a purposive sampling method. The results of this study prove that advertising, social media marketing, and product halalness have a positive and significant effect on increasing sales of Ms Glow Beauty. Advertising and social media not only increase sales, but also strengthen the perception of product halalness. In addition, product halalness is proven to be an important factor that mediates the influence of advertising on sales, so that advertising that emphasizes halal aspects can increase consumer trust and encourage purchases.